Daughters’ involvement and female succession in family businesses: A multiple case study - Floris, Michela; Dettori, Angela (Piccola Impresa / Small Business, 2022)
Drawing on the family embeddedness perspective, this study analyses women’s involvement in a dynamic perspective, investigating how motherhood, which occurred after succession, influenced daughters’ roles within the family business. Through a multiple case study of four small family-owned firms, our findings show four different treatments that women experienced when they became mothers after receiving the family firm’s baton.